Prevalence of excessive screen time and associated factors in adolescents - Lucena,Joana Marcela Sales de (2015)
Objective: To determine the prevalence of excessive screen time and to analyze associated factors among adolescents. Methods: This was a cross-sectional school-based epidemiological study with 2874 high school adolescents with age 14-19 years (57.8% female) from public and private schools in the city of João Pessoa, PB, Northeast Brazil. Excessive screen time was defined as watching television and playing video games or using the computer for more than 2 h/day. The associated factors analyzed were: sociodemographic (gender, age, economic class, and skin color), physical activity and nutritional status of adolescents. Results: The prevalence of excessive screen time was 79.5% (95%CI 78.1-81.1) and it was higher in males (84.3%) compared to females (76.1%; p<0.001). In multivariate analysis, adolescent males, those aged 14-15 year old and the highest economic class had higher chances of exposure to excessive screen time. The level of physical activity and nutritional status of adolescents were not associated with excessive screen time. Conclusions: The prevalence of excessive screen time was high and varied according to sociodemographic characteristics of adolescents. It is necessary to develop interventions to reduce the excessive screen time among adolescents, particularly in subgroups with higher exposure.